Nanoscale organic ferroelectric resistive switches - Khikhlovskyi, Vsevolod; Wang, Rui; Breemen, Albert J. J. M. van; Gelinck, Gerwin; Janssen, René A. J.; Kemerink, Martijn (The journal of physical chemistry. C, Energy, materials, and catalysis, 2014)
Organic ferroelectric resistive switches function by grace of nanoscale phase separation in a blend of a semiconducting and a ferroelectric polymer that is sandwiched between metallic electrodes. In this work, various scanning probe techniques are combined with numerical modeling to unravel their operational mechanism. Resistive switching is shown to result from modulation of the charge injection barrier at the semiconductor-electrode interfaces. The modulation is driven by the stray field of the polarization charges in the ferroelectric phase and consequently is restricted to regions where semiconductor and ferroelectric phases exist in close vicinity. Since each semiconductor domain can individually be switched and read out, a novel, nanoscale memory element is demonstrated. An ultimate information density of ∼30 Mb/cm2 is estimated for this bottom-up defined memory device.